THE INFLUENCE OF AUDIO-VISUAL VIDEO MEDIA ON KNOWLEDGE IN EFFORTS TO PREVENT SEXUAL VIOLENCE AGAINST ADOLESCENTS WITH DISABILITIES AT SLB SHANTI KOSALA NGANJUK - Kurniasari, Mia Ashari; Frenty Nurkhalim, Ratna (UNIVERSITAS AIRLANGGA, 2023)
Background: In Indonesia, teenagers account for one-quarter of the population. The focus of national development is on teenagers. Teenagers with disabilities are of particular concern due to their numerous restrictions, particularly in reproductive health education. They often experience health problems, especially sexual and reproductive health. Reproductive health education is the right solution for people with disabilities so that they can increase their knowledge in sexual violance so that they can protect themselves from a person. The aim of this research is to determine the effect of audio-visual video media on knowledge in efforts to prevent sexual violence among disabled teenagers. Method: We included all of the student that attend the school on the day of data collection. We used questionnaire to collect the data and the analytical test used was the Wilxocon Rank Test. Result: there was an increase in knowledge before implementing health education using audio-visual media, primarily 13.6%, with the high knowledge group comprising 54.5%. Meanwhile, the low knowledge group dropped from 86.4% to 45.5%. The Wilxocon Rank Test value is p= 0.035, indicating that audio-visual media has a significant influence on knowledge. Conclussion: There is an influence of audio-visual media with information in attempts to prevent sexual violence against disabled youth at SLB. Shanti Kosala Nganjuk.